Multiphoton Imaging of Renal Regulatory Mechanisms() - Peti-Peterdi, János (Physiology (Bethesda), 2009)
Most physiological functions of the kidneys, including the clearance of metabolic waste products, maintenance of body fluid, electrolyte homeostasis, and blood pressure, are achieved by complex interactions between multiple renal cell types and previously inaccessible structures in many organ parts that have been difficult to study. Multiphoton fluorescence microscopy offers a state-of-the-art imaging technique for deep optical sectioning of living tissues and organs with minimal deleterious effects. Dynamic regulatory processes and multiple functions in the intact kidney can be quantitatively visualized in real time, noninvasively, and with submicron resolution. This article reviews innovative multiphoton imaging technologies and their applications that provided the most complex, immediate, and dynamic portrayal of renal function—clearly depicting as well as analyzing the components and mechanisms involved in renal (patho)physiology.